EVALUATION OF DIET IN PATIENTS WITH HEPATIC DISEASES AFTER COVID 19 - Zakirhodjaev S. Y. (Web of Journals Publishing, 2025)
The COVID‑19 pandemic has had significant effects on patients with pre-existing liver diseases, influencing both disease progression and nutritional status. Proper dietary management is essential to support liver function, enhance immune response, and prevent further complications. This study evaluates the dietary habits, nutrient intake, and potential deficiencies in patients with hepatic diseases following COVID‑19 infection. Understanding these nutritional patterns can guide personalized dietary interventions to improve recovery and long-term liver health.
Keywords: Hepatic diseases, COVID‑19, Nutrition, Dietary evaluation, Liver function, Nutrient intake.